PHYTOCHEMICAL SCREENING OF ETHANOL EXTRACT 96% BLACK EAR MUSHROOM (Auricularia nigricans) BY SOXLETATION METHOD - Mercyska Suryandari, Mercyska; Andhika Dwi Aristyawan, Andika; Fiska Yuliarni, Floreta; Ari Anggraini, Nony (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2024)
Black ear mushroom (Auricularia nigricans) contains useful compounds, traditionally used as medicinal ingredients and food sources. The purpose of this study was to determine the secondary metabolites are contained in the extract of black ear mushroom (Auricularia nigricans). The extraction method used in this study is soxletation method. The sample used is 200 g of black ear mushroom (Auricularia nigricans) was extracted using soxhletation method with 1 l ethanol 96 % solvent. The phytochemical screenings test uses standard reagent by observing color changes, sediment, and foam. The result of the study that the extract of black ear mushroom (Auricularia nigricans) showed a red color after being given Dragendorrf reagent, terpenoid reagent test, flavonoid reagent test, gave a green color change after being given phenolic and tannin reagent test, did not give a red color in the steroid reagent test and did not produce foam in the saponin test. The conclusion of the study that the extract of black ear mushroom (Auricularia nigricans) contained secondary metabolite compounds tannins, terpenoids, flavonoids, phenolics, and alkaloids.